Pengaruh Penerapan Sistem Akuntansi Keuang Daerah, Komitmen Organisasi dan Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Reza Ilham Putra; Halmawati Halmawati (Universitas Negeri Padang, 2022)
This study aims to determine the effect of application of regional financial accounting systems, organizational commitment and internal control systems on the quality of the financial statements of the local government of Solok City. This study uses primary data obtained by distributing questionnaires to 24 SKPD within the Solok City Government with a total of 48 questionnaires distributed and each SKPD consisting of 2 samples. The sample in this study are employees who are responsible for making local government financial reports. The selection of respondents using purposive sampling method. The results of the study indicate that The SAKD variable has an effect on the LKPD quality variable. The organizational commitment variable has no effect on the LKPD quality variable. SPI has no effect on the quality of LKPD.The results of this study can be used as an evaluation and consideration for the SKPD of Solok City in the process of preparing financial reports in order to achieve good quality financial reports. This can be done by improving the implementation of the regional financial accounting system properly.